2016
DOI: 10.1021/acs.est.5b05559
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Sealing with Microbially-Induced Calcium Carbonate Precipitation: A Field Study

Abstract: A primary environmental risk from unconventional oil and gas development or carbon sequestration is subsurface fluid leakage in the near wellbore environment. A potential solution to remediate leakage pathways is to promote microbially induced calcium carbonate precipitation (MICP) to plug fractures and reduce permeability in porous materials. The advantage of microbially induced calcium carbonate precipitation (MICP) over cement-based sealants is that the solutions used to promote MICP are aqueous. MICP solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(107 citation statements)
references
References 31 publications
2
105
0
Order By: Relevance
“…The effect of nutrient conditions also promoted the survival and dominancy of S. pasteurii UB confirming the successful survival and competence of this culture in presence of other native communities. Recent reports of Phillips et al (2016) also confirmed the survival of augmented Sporosarcina pasteurii in deep soils where it successfully overtook native Pseudomonas sp. This study further confirms the promising potential of this culture for several bio-engineering applications involving augmentation.…”
Section: Resultsmentioning
confidence: 74%
“…The effect of nutrient conditions also promoted the survival and dominancy of S. pasteurii UB confirming the successful survival and competence of this culture in presence of other native communities. Recent reports of Phillips et al (2016) also confirmed the survival of augmented Sporosarcina pasteurii in deep soils where it successfully overtook native Pseudomonas sp. This study further confirms the promising potential of this culture for several bio-engineering applications involving augmentation.…”
Section: Resultsmentioning
confidence: 74%
“…Measured fluid elemental concentrations for both wells are listed at left. calcium have been co-injected with microbial suspensions to successfully induce carbonate biomineralization of injected CO 2 as a plume containment strategy (Phillips et al, 2016). In the context of GCS management considerations, the taxa and associated genomic content detected within the McElmo Dome system may thus inform the types of in situ or introduced microbial diversity and nutrient profiles required to exploit metabolic and geochemical potential for safe, long-term CO 2 sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…7H 2 O, 0.27-g CaCl 2 , 0.5-g KH 2 PO 4 distilled water 100 mL) in order to screen its urease producing ability. [2] Optimization procedure and experimental design Investigation of factors affecting urease production Initial screening was carried out to find the best source of carbon (glucose, fructose, sucrose, lactose, starch and mannitol) and nitrogen (beef extract, yeast extract, peptone, casein, ammonium sulfate and sodium nitrate); those have stimulatory impact on urease production along with incubation time (12-144 h), temperature (25-65°C) and pH (6)(7)(8)(9)(10).The inoculum concentration was also varied from 5 × 10 6 cells mL À1 to 5 × 10 9 cells mL À1 . This was followed by employing the PB design to screen significant factors among all which affect the production of urease in B. megaterium SS3.…”
Section: Methodsmentioning
confidence: 99%
“…The promising results on restoration of cement mortar cubes, reduction of water and chloride ion permeability in concrete, remediation of cracks in concrete, sand consolidation and limestone monument repair, increase in strength of red bricks have been proved by number of researchers. [7,8] This technology has also revealed few successful field trials and is becoming more and more acceptable because of its highly sustainable nature which puts more pressure on higher production of microbial carbonates through alternative microbial routes. One such route can be higher production of urease enzyme by ureolytic bacteria which play a direct role in carbonate production.…”
Section: Introductionmentioning
confidence: 99%